Notes on the Reconstruction of the Proto-Indo-European Genitive and Locative Dual - Luka (Jezikoslovni zapiski, 2025)
This article focuses on the formation of the Proto-Indo-European genitive and locative dual and defines the main lines in the development of the two case forms in the individual Indo-European languages (Ancient Greek, Old Indo-Iranian, Balto-Slavic, Old Irish, Germanic, and Tocharian). It does so by combining external and internal reconstruction. Special attention is devoted to the interplay between the pronominal and nominal stems.